Trade, Climate Policy and Carbon Leakage - Theory and Empirical Evidence - Rahel Aichele (ifo Institut - Leibniz-Institut für Wirtschaftsforschung an der Universität München, 2013)
This volume was prepared by Rahel Aichele while she was working at the ifo Institute. It was completed in December 2012 and accepted as a doctoral thesis by the Department of Economics at the University of Munich. It includes five self-contained chapters. The chapters investigate how, in a globalized world, partial international climate policy has shaped international trade and the location of emissions. The main research question is whether carbon leakage empirically occurs, thus undermining the effectiveness of unilateral climate policy. The thesis provides new empirical tests for leakage based on a newly developed panel dataset of the carbon content of bilateral trade and country-level carbon footprints for 40 countries over the period 1995-2007. The Kyoto Protocol constitutes a quasi-natural experiment of international climate policy. We exploit policy evaluation techniques to study its effects on CO2 emissions (Chapter 1), carbon footprints (Chapter 2), trade values (Chapter 3) and the carbon content of trade (Chapter 4). To deal with self-selection into treatment, fixed-effects, instrumental variables or matching econometrics techniques are employed. We find empirical evidence for carbon leakage in the data. The extent of carbon leakage is then quantified with a structurally estimated trade model (Chapter 5). Simulations of counterfactual climate policy scenarios show moderate but non-negligible leakage rates.
Keywords: C26; F18; F53; Q48; Q54; Q56; Q58; 330; Carbon content of trade; carbon footprint; carbon leakage; climate policy; CO2 emission; competitiveness; energy; evaluation model; gravity equation; instrumental variables; international trade; Kyoto Protocol; matching econometrics; treatment effects; Internationale Wirtschaft; Treibhausgas-Emissionen; Klimaschutz; Auslandsverlagerung; Standortwahl; Welt